Property-governed performance of platinum-modified titania photocatalysts - Wang, Kunlei; Kowalska, Ewa (Frontiers in Chemistry, 2022)
Titania is probably the most widely investigated semiconductor photocatalyst because of various advantages, such as high activity, thermal and chemical stability, low price, abundance, and negligible toxicity. However, pristine titania is also characterized by charge carriers’ recombination, and thus lower quantum yields of photocatalytic reactions than theoretical 100%. Moreover, its wide bandgap, despite being recommended for excellent redox properties, means also inactivity under visible part of solar radiation. Accordingly, titania has been surface modified, doped and coupled with various elements/compounds. For example, platinum deposited on the surface of titania has shown to improve both UV activity and the performance under vis. Although the studies on titania modification with platinum started almost half a century ago, and huge number of papers have been published up to now, it is unclear which properties are the most crucial and recommended to obtain highly efficient photocatalyst. In the literature, the opposite findings could be found on the property-governed activities that could result from huge differences in the reaction systems, and also examined photocatalysts. Considering the platinum properties, its content, the size of nanoparticles and the oxidation state, must be examined. Obviously, the characteristics of titania also influence the resultant properties of deposited platinum, and thus the overall photocatalytic performance. Although so many reports on Pt/TiO2 have been published, it is hardly possible to give indispensable advice on the recommended properties. However, it might be concluded that usually fine platinum NPs uniformly deposited on the titania surface result in high photocatalytic activity, and thus in the low optimal content of necessary platinum. Moreover, the aggregation of titania particles might also help in the lowering the necessary platinum amount (even to 0.2 wt%) due to the interparticle electron transfer mechanism between titania particles in one aggregate. In respect of platinum state, it is thought that it is highly substrate-specific case, and thus either positively charged or zero valent platinum is the most recommended. It might be concluded that despite huge number of papers published on platinum-modified titania, there is still a lack of comprehensive study showing the direct correlation between only one property and the resultant photocatalytic activity.